Increasing elementary school teachers' awareness of gender inequity in student computer usage - Nicole Luongo (International Electronic Journal of Elementary Education, 2012)
This study was designed to increase gender equity awareness in elementary school teachers with respect to student computer and technology usage. Using professional development methods with a group of teachers, the writer attempted to help them become more aware of gender bias in technology instruction. An analysis of the data revealed that teachers who were exposed to gender equity professional development training sessions were more likely to exhibit gender equitable teaching behaviors than they did prior to the sessions. The data also indicated that teachers provided more equitable assistance to their classroom students after being presented with gender equity interventions.